Conspiracy theory and cognitive style: a worldview - Dagnall, Neil; Drinkwater, Kenneth; Parker, Andrew; Denovan, Andrew; Parton, Megan (Frontiers in Psychology, 2015)
This paper assessed whether belief in conspiracy theories was associated with a particularly cognitive style (worldview). The sample comprised 223 volunteers recruited via convenience sampling and included undergraduates, postgraduates, university employees and alumni. Respondents completed measures assessing a range of cognitive-perceptual factors (schizotypy, delusional ideation and hallucination proneness) and conspiratorial beliefs (general attitudes towards conspiracist thinking and endorsement of individual conspiracies). Positive symptoms of schizotypy, particularly the cognitive-perceptual factor, correlated positively with conspiracist beliefs. The best predictor of belief in conspiracies was delusional ideation. Consistent with the notion of a coherent conspiratorial mindset, scores across conspiracy measures correlated strongly. Whilst findings supported the view that belief in conspiracies, within the sub-clinical population, was associated with a delusional thinking style, cognitive-perceptual factors in combination accounted for only 32% of the variance.